Compressive Properties Of Jute/Kevlar Under Static And Impact Loading - Rosli, Fadlhlin Sakina (Universiti Sains Malaysia, 2022)
Hybrid composite are in high demand due to their superior qualities. Natural fibres have good mechanical qualities and are less expensive than synthetic fibres, providing them a potential alternative to synthetic fibers. Due to problems such as their lower impact strength, researchers concentrated on integrating these two fibres as an alternative to overcome the single fibre's limitations. Thus, this analysis focused on the hybridisation of natural and synthetic fibres with the effect of static and impact loading towards the layer sequence and the mechanical properties of Jute–Kevlar- epoxy-based hybrid composite. The composite samples of jute and Kevlar are prepared to have four different layup configurations (i.e., Jute-Jute-Jute [JF], Jute-Kevlar-Jute [H1], Kevlar-Jute-Kevlar [H2], and Kevlar-Kevlar-Kevlar [KVF]). The mechanical properties of the composites like compressive strength have been evaluated. According to the results obtained, the material behaviour or mechanical properties of composites are considerably affected by layer sequences. It is found that between the four types of layup configuration, jute fiber (JF) has the highest compressive strength compared to full Kevlar (KVF), Hybrid jute (H1) and hybrid Kevlar (H2) under dynamic loading. Kevlar has the lowest compressive strength, which indicate low compressive strength, which can lead to the separation of layers within a laminate under compression. However, under static loading, hybrid jute (H1) shows the highest compressive strength, while, hybrid Kevlar (H2) has the lowest compressive strength. The failures mode of the specimens is also observed in this experiment using Scanning Electron microscopic (SEM). Under static loading, the damages were primarily of delamination, fibre breakage, interfacial debonding, and fibre pull-out, while the failure of the high strain rate condition consisted primarily of kink band, fibre breakage, fibre matrix debonding, edge failure, and fibre thinning.